Efeito do tratamento com o monoterpeno sintético 4-carvomenthenol em modelo experimental da síndrome da asma e rinite alérgicas combinadas (CARAS) - Barros, Grasiela Costa Bezerra (2021)
4-carvomenthenol (Carvo) or terpinene-4-ol is a monoterpene present in essential oils from pharmacologically active aromatic plants. Therapeutic activities include anti-inflammatory and immunomodulatory properties. Asthma and allergic rhinitis are chronic airway diseases that coexist with high global prevalence, generating negative economic and social impacts. To control both diseases, the drug combination is used unsuccessfully in several patients, in addition to generating serious side effects. This study aimed to analyze oral treatment with Carvo in the experimental model of Combined Asthma and Allergic Rhinitis Syndrome (CARAS). BALB/c mice were sensitized with ovalbumin (OVA) on day zero and seventh (50 μg / mL OVA in 10 mg/mL Al (OH) 3) and challenged by OVA (5 mg / mL, 20 μL / animal) for three weeks. In the last week, the animals were challenged with an OVA aerosol and the treatment with Carvo (12.5, 25, or 50 mg/kg) occurred one hour before each OVA challenge. Data were analyzed and p <0.05 was considered significant. Carvo (12.5-50 mg/kg) decreased the migration of eosinophils in the upper (NALF) and lower (BALF) airways, as well as in the nasal and lung tissues of sick animals. The treatment also decreased mucus production in both tissue sections stained with PAS (periodic acid-Schiff). Histological analyzes showed that sick mice showed hyperplasia and hypertrophy of the smooth muscle layer of the lung, followed by an increase in the extracellular matrix, however, Carvo (50 mg/kg) inhibited these asthmatic parameters. The signs of allergic rhinitis, such as nasal rubs and sneezing, were analyzed and it was observed that the Carvo decreased these two nasal signs, as well as the specific IgE-OVA titer, and the cytokine IL-13, with an increase in IL-10. The decrease in IL-13 production corroborated with the decrease in mucus production and these effects were dependent on the inhibition of the p38MAPK / NF-κB signaling pathway (p65). Therefore, these data demonstrated that 4- Carvomenthenol has antiallergic properties in an experimental model of CARAS, suggesting a new drug prototype for the treatment of this allergic syndrome.